STATISTICS OF ACCIDENT AND MEASURES TO REDUCE EMERGENCY FOR THE TRANSPORTATION OF DANGEROUS GOODS - A. Ochkalova (Вестник университета)
The article describes the definition of dangerous goods, shows the reasons for the increased control over the transportation of such kind of goods and special security measures, shows the statistics of accidents in the transportation of dangerous goods in Russia, gives examples of different intellectual systems, providing control over the transportation of dangerous goods, presents using such kind of systems abroad, and shows a need for further measures to ensure safety transportation of dangerous goods.